اهمية البروبيوتيك في الانسان والحيوان (مجلة الرازي الطبية, 2025)
https://docs.google.com/document/d/1tF-ZIpUhILEhhDvDvkzoxYevbuvpOYtx/edit?usp=drive_link&ouid=103238479149704124457&rtpof=true&sd=true
Keywords: البروبيوتيك العصية اللبنية، البيفيدوباكتيريا